2020
DOI: 10.1016/j.scitotenv.2020.139085
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 partial lockdown on the air quality of the city of Rio de Janeiro, Brazil

Abstract: CO levels showed the most significant reductions during the partial lockdown.• NO 2 decreased in a lower extent, due to industrial and diesel input. • PM 10 levels were only reduced during the first partial lockout week. • Ozone increased due to the decrease in nitrogen oxides level in a VOCcontrolled scenario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

67
474
5
35

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 576 publications
(609 citation statements)
references
References 13 publications
67
474
5
35
Order By: Relevance
“…• SO2 is negatively related to COVID-19 cases. (Dantas, Siciliano, França, da Silva, & Arbilla, (2020) • PM10…”
Section: Chinamentioning
confidence: 99%
“…• SO2 is negatively related to COVID-19 cases. (Dantas, Siciliano, França, da Silva, & Arbilla, (2020) • PM10…”
Section: Chinamentioning
confidence: 99%
“…Contemporarily, many scholars have carried out relevant researches in the world. (Dantas et al 2020;Lal et al 2020;Li et al 2020;Nakada and Urban 2020) found that the lockdown reduces the emissions of SO 2 , NO x , PM 2.5 , CO, VOCs, and AQI, even low-to-moderate reduce Aerosol Optical Depth obviously in the corresponding research region. But at the same time, some of them found that ozone increased distinctly.…”
Section: Introductionmentioning
confidence: 99%
“…Italy (Cristina et al 2020;Muhammad et al 2020;Zambrano-monserrate et al 2020), Spain, France (Muhammad et al 2020;Zambrano-monserrate et al 2020), USA (Muhammad et al 2020), Germany (Zambrano-monserrate et al 2020), Brazil (Dantas et al 2020), Kazakhstan (Kerimray et al 2020), etc.…”
Section: Introductionmentioning
confidence: 99%
“…The control on construction-related activities could also have contributed to the decrement observed in PM 2.5 and PM 10 concentrations. The decrease in ambient sulfur-di-oxide (SO 2 ) concentration during the control period was proportional to the decreased emission from industrial activities (Dantas et al 2020;Mahato et al 2020;Wang et al 2020b). Although there was a decrease in air pollution in many countries of the world during lockdown, restricted anthropogenic activities were not su cient alone to explain the reduction in the level of pollutants in air.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation